SPE Asia Pacific Oil &Amp; Gas Conference and Exhibition 2014
DOI: 10.2118/171529-ms
|View full text |Cite
|
Sign up to set email alerts
|

Wettability Alteration during Low-Salinity Waterflooding in Carbonate Reservoir Cores

Abstract: Production enhancement by low-salinity waterflood in carbonate formations is a subject of intense speculation. Several mechanisms are attributed to enhanced oil recovery by low-salinity waterflooding in carbonate formations. Review of experimental data in the literature indicates that the main mechanism involves interaction of Na+, Cl−, Ca2+, Mg2+, SO42− and crude oil carboxylate ions (R-COO−) with the rock in the electrical double layer (EDL) near the surface of carbonate pores, leading to wettability alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 13 publications
5
48
0
Order By: Relevance
“…Our results are in agreement with Rezaei et al [67], who reported that increasing the pH of n-decane (non-polar oil)-brine-calcite system from 5 to 10 reduces the contact angle from 148° to 51°, suggesting that the wettability of n-decane-brine-calcite system is dependent on pH. Alameri et al [13] also reported a similar pH effect on the contact angle of the oil-brine-carbonate system. It is also worth noting that pH likely significantly affects the interaction of the polar-oil-brinecarbonate system, and thus contact angle and wettability.…”
Section: Effect Of Ph On the Contact Angle Of The Non-polar Oil-brinesupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are in agreement with Rezaei et al [67], who reported that increasing the pH of n-decane (non-polar oil)-brine-calcite system from 5 to 10 reduces the contact angle from 148° to 51°, suggesting that the wettability of n-decane-brine-calcite system is dependent on pH. Alameri et al [13] also reported a similar pH effect on the contact angle of the oil-brine-carbonate system. It is also worth noting that pH likely significantly affects the interaction of the polar-oil-brinecarbonate system, and thus contact angle and wettability.…”
Section: Effect Of Ph On the Contact Angle Of The Non-polar Oil-brinesupporting
confidence: 92%
“…Extensive research has been done to show that lowering injected brine salinity can improve oil recovery from carbonate reservoir at secondary and tertiary mode from 5 to 30% of the original oil in place (OOIP) [5][6][7][8][9][10][11][12]. Wettability alteration towards a more water-wet state is believed to be one of the main physiochemical processes behind the low salinity effect, which shifts oil relative permeability towards a lower residual oil saturation [9,[13][14][15], thus enhancing oil recovery. To understand the factors controlling the wettability alteration process in carbonate reservoirs, several explanations have been developed and proposed to predict and quantify the wettability alteration, such as electrostatic bridging [7,8,[16][17][18], electrical double layer [13,[19][20][21], and surface complexation modelling [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These different scales of investigation have been well tested, though some were more tested compared to others, many of which will be discussed below. However, studies [26,[34][35][36][37] that reported interfacial tension measurements were not highlighted in this review because changes in the brine-oil interfacial tension observed is considerably less to associate the recovery process to IFT reduction compared to those associated with gas-dependent recovery processes and alkaline waterflooding. Based on these previous studies, various aspects of the experimental method have been investigated, including reservoir and the injected brine parameters, to identify the optimum condition for brine-dependent process performance.…”
Section: Laboratory Experimental Studiesmentioning
confidence: 99%
“…As discussed above, sandstone reservoirs were the focus of several studies on the effect of initial wettability on oil recovery. However, very few studies have been reported on carbonates [21][22][23], and the investigation process has yet to give rise to a definitive conclusion regarding carbonate reservoirs. The potential of LSW in carbonate reservoirs has been proven and it was observed that wettability alteration is the main mechanism of LSW/smart water injection.…”
Section: Introductionmentioning
confidence: 99%